Surveillance of Amphotericin B and Azole Resistance in Aspergillus Isolated from Patients in a Tertiary Teaching Hospital - Lívia Maria Maciel da Fonseca; Vanessa Fávaro Braga; Ludmilla Tonani; Patrícia Helena Grizante Barião; Erika Nascimento; Roberto Martinez; Marcia Regina von Zeska Kress (Journal of Fungi, 2023)
The genus Aspergillus harbors human infection-causing pathogens and is involved in the complex one-health challenge of antifungal resistance. Here, a 6-year retrospective study was conducted with Aspergillus spp. isolated from patients with invasive, chronic, and clinically suspected aspergillosis in a tertiary teaching hospital. A total of 64 Aspergillus spp. clinical isolates were investigated regarding molecular identification, biofilm, virulence in Galleria mellonella, antifungal susceptibility, and resistance to amphotericin B and azoles. Aspergillus section Fumigati (A. fumigatus sensu stricto, 62.5%) and section Flavi (A. flavus, 20.3%; A. parasiticus, 14%; and A. tamarii, 3.1%) have been identified. Aspergillus section Flavi clinical isolates were more virulent than section Fumigati clinical isolates. Furthermore, scant evidence supports a link between biofilm formation and virulence. The susceptibility of the Aspergillus spp. clinical isolates to itraconazole, posaconazole, voriconazole, and amphotericin B was evaluated. Most Aspergillus spp. clinical isolates (67.2%) had an AMB MIC value equal to or above 2 µg/mL, warning of a higher probability of therapeutic failure in the region under study. In general, the triazoles presented MIC values above the epidemiological cutoff value. The high triazole MIC values of A. fumigatus s.s. clinical isolates were investigated by sequencing the promoter region and cyp51A locus. The Cyp51A amino acid substitutions F46Y, M172V, N248T, N248K, D255E, and E427K were globally detected in 47.5% of A. fumigatus s.s. clinical isolates, and most of them are associated with high triazole MICs. Even so, the findings support voriconazole or itraconazole as the first therapeutic choice for treating Aspergillus infections. This study emphasizes the significance of continued surveillance of Aspergillus spp. infections to help overcome the gap in knowledge of the global fungal burden of infections and antifungal resistance, supporting public health initiatives.